(untitled) (The Review of Diabetic Studies, 2023)
The impact of strict glycemic control on the prevention of macrovascular diseases in type 2 diabetes patients has remained unresolved for decades. New results presented at the EASD meeting shed new light on this question. Recent data from the United Kingdom Prospective Diabetes Study (UKPDS) showed that intensive glycemic control, when initiated immediately after diagnosis of type 2 diabetes and continued for a period of ten years followed by another ten years without special intervention, prevents myocardial infarction and decreases all-cause mortality. The Veterans Affairs Diabetes Trial demonstrated that striving to achieve near-normal glycemia in older patients with relatively long duration of diabetes and, in many cases, previous macrovascular events did not reduce future macrovascular events but increased the risk of severe hypoglycemia. These results indicate that effective treatment of hyperglycemia should be started early after diabetes diagnosis. However, introducing strict diabetes control after more than 10 years diabetes duration may lead to unfavorable effects in patients with hitherto unsatisfactorily controlled diabetes.